Genotype variability and stability in seed and forage yields of cowpea under Gezira conditions - Abd Elrhman, Babiker; Meseka, Silvestro; Ali, Eltahir; Ibrahim, Abu Elhassan (Gezira Journal of Agricultural Science; Vol 8 No 1 (2010), 2010)
76       An experiment was conducted for three consecutive seasons (summer, autumn and winter) in 2006 at Gezira University Farm, Wad Medani, Sudan, to estimate stability and genetic variability of seed and forage yields and their components in 15 cowpea ( Vigna unguiculata (L.) Walp) genotypes. Plant height, days to first flowering, days to 50% flowering, days to pod maturity, number of pods per plant, pod weight, 100-seed weight, seed yield, fresh forage yield and harvest index were measured in autumn, while only seed and forage yields were measured in summer and winter. Analysis of autumn season only showed significant differences among genotypes for all studied characters. High broad sense heritability estimates (>80%) were recorded for plant height, days to first flowering, number of pods per plant, pod weight, fresh forage yield and harvest index. Autumn was the best of the three seasons in terms of seed yield, suggesting that most of the genotypes responded relatively better under rainfed conditions than irrigated, whereas summer was the best in terms of fresh forage yield. Seed yield stability estimates revealed that IT98K-412-13 and IT98K-131-2 were the most stable genotypes for seed yield, while, IT89KD-288 and IT95K-52-34 were the most stable genotypes for forage yield. Two genotypes, IT95K-52-34 and IT98K-311-8-2, were identified as dual purpose (forage and seed) genotypes. These two genotypes would fit well in the Sudanese agricultural system where cowpea is being grown both for food and animal feed.     أجريت التجربة لثلاثة مواسم متتالية (صيف، خريف و شتاء 2006) في مزرعة جامعة الجزيرة، وادمدني، السودان، لتحديد مقدار الثبات والاختلاف الوراثي لإنتاج البذور والعلف ومكوناتهما في 15 سلاله لوبيا حلو. استخدم تصميم القطاعات العشوائية الكاملة بثلاث مكررات. تم قياس صفتي إنتاج البذور و العلف في المواسم الثلاثة وفى الخريف فقط تم قياس صفات ارتفاع النبات، الأيام حتى بداية الأزهار، الأيام حتى 50% أزهار، الأيام حتى نضج القرون، عدد القرون في النبات الواحد، وزن القرون، وزن ال100 حبه ودليل الحصاد . أظهرت النتائج اختلافا كبيرا بين السلالات في معظم الصفات المدروسة. أعلى نسبه لدرجة التوريث على النطاق العريض (أكثر من 80%) سجلت لطول النبات، الأيام حتى الأزهار، عدد القرون في النبات الواحد، وزن القرن، إنتاجية البذور والأعلاف الخضراء ودليل الحصاد. كان التفاعل بين السلالات والبيئة معنوياً لكل من إنتاجية البذور والعلف. أظهرت الدراسة بان السلالتين  IT98K-311-8-2, IT95K-52-34   يمكن أن يستخدما لإنتاج العلف و البذور وكانت أعلى السلالات إنتاجاً للبذور IT98K-311-8-2, IT98K131-2, IT95K-52-34, IT97K-461-4, IT99K-7-212-2 والبلدي والتي تتراوح في الإنتاج ما بين 619.79 و 413.78 كجم/هـ وان أعلى السلالات إنتاجاً للعلف الأخضر كانت IT89K-288, IT95K-52-34, IT98K-311-8-2, IT96D-733, IT98K-412-8 والتي تتراوح إنتاجيتها بين 8577.0 و 7612.7 كجم/هـ.